Ultrasound-Assisted Extraction of Total Phenolic Compounds from Inula helenium - Jin Wang; Yong-Ming Zhao; Ya-Ting Tian; Chun-Lin Yan; Chun-Yan Guo (The Scientific World Journal)
Ultrasound-assisted extraction (UAE) of phenolic compounds from Inula helenium was studied. Effects of ethanol concentration, ultrasonic time, solid-liquid ratio, and number of extractions were investigated. An orthogonal array was constructed to optimize UAE process. The optimized extraction conditions were as follows: ethanol concentration, 30%; solid-liquid ratio, 1 : 20; number of extractions, 2 times; extraction time, 30 min. Under the optimal conditions, the yield of total phenolic compounds and chlorogenic acid was 6.13±0.58 and 1.32±0.17 mg/g, respectively. The results showed that high amounts of phenolic compounds can be extracted from I. helenium by ultrasound-assisted extraction technology.